Using photography to explore people with diabetes' perspectives on food environments in urban and rural South Africa. (3rd May 2020) - Spires, Mark; Delobelle, Peter; Sanders, David; Puoane, Thandi
Abstract: Diabetes, a serious disease resulting in significant morbidity and early mortality, is currently on the rise globally. A major contributor to this observed increase in low- and middle-income countries, such as South Africa, has been the observed change in diet at the population level—a shift from a traditional diet, to one consisting of more energy-dense, processed foods, with more added sugar, salt and fat. Implicated in this degradation of diet are changing local food environments. Participant-generated digital photographs and facilitated focus group discussion-style workshops were utilized to better understand diabetic community members' perspectives on their food environments in both an urban and rural setting in South Africa, and what (and how) aspects of these physical environments influence their food acquisition behaviours and diet. Qualitative data were analysed using a deductive thematic analysis approach. The resulting predominant themes of accessibility, availability and affordability are outlined and discussed. Findings from this study have implications beyond the self-management of diabetes and extend to the self-management and reduction of all diet-related non-communicable diseases.